Prosedur Perpanjangan Endorsement Surat Laut Mv. Eastern Fair pada PT. Multi Jaya Samudera Belawan - Heru Hermawan Sibarani; Syarifur Ridho; Lilis Lilis (Jurnal Pemimpin Bisnis Inovatif, 2025)
The Sea Certificate (Surat Laut/SL) is a crucial maritime legal document, serving as proof of a ship's nationality and its seaworthiness status for sailing, making it a mandatory requirement in every clearance in and clearance out process. This research aims to comprehensively identify and analyze the procedure for the endorsement (validation) extension of the Sea Certificate for the MV. Eastern Fair, carried out by PT. Multi Jaya Samudera as the ship agent in Belawan. The research method utilized is field research, conducted through land practice (PRADA), interviews, and documentation study. The findings indicate that the endorsement extension procedure is executed through a strict series of stages, starting from the preparation of the ship's technical documents to the official submission to relevant agencies such as the Harbor Master (Syahbandar) and the Transportation Agency Office. The ship agent plays a vital role as the liaison and executor, responsible for ensuring the completeness and validity of all administrative requirements within the specified timeframe. Although the procedure is standardized, common constraints include delays from related parties, both in physical inspection and administrative completion at government institutions, which can potentially disrupt the vessel’s sailing schedule. This study concludes that rigorous supervision and effective coordination among the agent, ship owner, and port authorities are key to maintaining regulatory compliance and the operational smooth running of the MV. Eastern Fair.